Virtual Reality for Physics Learning: A Thematic Review with Cross-Disciplinary Insights on Effectiveness, Immersion, Instructional Design, and Implementation Challenges - Dosol-Demonteverde, Mailah Grace; Barrios, Rubilyn G (Lensa: Jurnal Kependidikan Fisika, 2026)
Virtual reality (VR) has gained increasing attention in education, particularly for learning contexts that involve abstract concepts, dynamic processes, and simulation-based experiences. This study presents a structured thematic review of 33 Scopus-indexed articles published between 2021 and 2026, focusing on physics learning while incorporating cross-disciplinary studies as conceptual support. The review examined five major themes: effectiveness in improving learning outcomes and conceptual understanding, immersion and embodiment, suitability for abstract and high-risk contexts, the role of instructional design and usability, and implementation challenges and future directions. The findings indicate that VR is especially beneficial for physics topics such as projectile motion, quantum physics, the photoelectric effect, electric fields, and virtual laboratory activities, where visualization and interaction are essential. Across the reviewed studies, VR was consistently associated with gains in conceptual understanding, engagement, retention, motivation, and learner confidence, although these effects were conditional rather than universal. The review also shows that immersion alone is insufficient; educational effectiveness depends heavily on instructional coherence, usability, intuitive interaction, and contextual fit. Despite its promise, broader implementation remains constrained by cost, infrastructure, teacher readiness, and uneven methodological quality. Overall, VR emerges as a powerful but context-sensitive pedagogical approach for physics learning in contemporary educational and training settings.